Preparation and Optical Properties of GeBi Films by Using Molecular Beam Epitaxy Method - Dainan Zhang; Yulong Liao; Lichuan Jin; Qi-Ye Wen; Zhiyong Zhong; Tianlong Wen; John Q. Xiao (Nanoscale Research Letters, 2017)
Abstract Ge-based alloys have drawn great interest as promising materials for their superior visible to infrared photoelectric performances. In this study, we report the preparation and optical properties of germanium-bismuth (Ge1-xBix) thin films by using molecular beam epitaxy (MBE). GeBi thin films belong to the n-type conductivity semiconductors, which have been rarely reported. With the increasing Bi-doping content from 2 to 22.2%, a series of Ge1-xBix thin film samples were obtained and characterized by X-ray diffraction, scanning electron microscopy, and atomic force microscopy. With the increase of Bi content, the mismatch of lattice constants increases, and the GeBi film shifts from direct energy band-gaps to indirect band-gaps. The moderate increase of Bi content reduces optical reflectance and promotes the transmittance of extinction coefficient in infrared wavelengths. The absorption and transmittance of GeBi films in THz band increase with the increase of Bi contents.